Genetic ablation of Toll‐like Receptor 4 seems to activate the apoptosis pathway in the skeletal muscle of mice after acute physical exercise. (22nd November 2022) - Marafon, Bruno B.; Pinto, Ana P.; de Vicente, Larissa G.; da Rocha, Alisson L.; Simabuco, Fernando M.; Ropelle, Eduardo R.; de Moura, Leandro P.; Cintra, Dennys E.; Pauli, José R.; Silva, Adelino S. R. da
Abstract: Many conditions, such as inflammation and physical exercise, can induce endoplasmic reticulum (ER) stress. Toll‐like Receptor 4 (TLR4) can trigger inflammation and ER stress events. However, there are still no data in the literature regarding the role of TLR4 in ER stress during exercise in skeletal muscle. Therefore, the current investigation aimed to verify the responses of ER stress markers in wild‐type (WT) and Tlr4 global knockout (KO) mice after acute and chronic physical exercise protocols. Eight‐week‐old male WT and KO mice were submitted to acute (moderate or high intensity) and chronic (4‐week protocol) treadmill exercises. Under basal conditions, KO mice showed lower performance in the rotarod test. Acute high‐intensity exercise increased eIF2α protein in the WT group. After the acute high‐intensity exercise, there was an increase in Casp3 and Ddit3 mRNA for the KO mice. Acute moderate exercise increased the cleaved Caspase‐3/Caspase‐3 in the KO group. In response to chronic exercise, the KO group showed no improvement in any performance evaluation. The 4‐week chronic protocol did not generate changes in ATF6, CHOP, p‐IRE1α, p‐eIF2α/eIF2α, and cleaved Caspase‐3/Caspase‐3 ratio but reduced BiP protein compared with the KO‐Sedentary group. These results demonstrate the global deletion of Tlr4 seems to have the same effects on UPR markers of WT animals after acute and chronic exercise protocols but decreased performance. The cleaved Caspase‐3/Caspase‐3 ratio may be activated by another pathway other than ER stress in Tlr4 KO animals. Key points: While acute high‐intensity exercise increased the Casp3 and Ddit3 mRNA in KO mice, acute moderate‐intensity exercise increased the cleaved Caspase‐3/Caspase‐3 in the same group. Under basal conditions, Tlr4 KO mice showed lower performance in the rotarod test. In response to chronic exercise, the Tlr4 KO group showed no improvement in any performance evaluation. The global deletion of Tlr4 seems to have the same effects on UPR markers of WT animals after acute and chronic exercise protocols but decreased performance and seems to activate the apoptosis pathway. Significance statement The endoplasmic reticulum (ER) is responsible for translating and folding most proteins in our body. Protein homeostasis imbalance leads to malformed proteins in the ER lumen, and their accumulation leads to ER stress. Toll‐like Receptor 4 (TLR4) can trigger inflammation, and TLR4 global knockout (KO) mice are protected against ER stress. Furthermore, physical exercise can reduce the TLR4 in the cell. As inflammation seems to affect physical exercise‐related ER stress, the present study investigated the relationship between TLR4 and ER stress after physical exercise in skeletal muscle.